Smart Cities Digital Transformation: Funded by Tufidco in Tamil Nadu (Global Journal of Management and Business Research, 2023)
In India the smart cities projects were implemented by Indian government. In Tamil Nadu many states are selected to convert cities into smart cities. TUFIDCO is providing financial assistance to smart cities projects. The digital Transformation is the vital part in smart cities projects. The main aim of Tamil Nadu Urban Finance and Infrastructure Development Corporation Limited mission is to provide financial assistance and guidance to Local Bodies, Corporations, Boards, Authorities, and parastatal agencies for their development projects. An intelligent city refers that provides all the facilities a city needs, such as education, electricity, transportation, green environments, good governance and information technologies. To put it simply, smart cities improve the quality of life. The selected Smart Cities are Chennai, Coimbatore, Madurai, Thanjavur, Salem, Vellore, Tiruppur, Thoothukudi, Tirunelveli, Tiruchirappalli and Erode in Tamil Nadu. Researchers obtain data from secondary sources. In order to carry out this research, the researcher should analyze the
Keywords: TUFIDCO; smart cities; cost; project; financial assistance; digital transformation